What are the environmental impacts of property rights regimes in forests, fisheries and rangelands?: a systematic review protocol - Ojanen, M.; Miller, D.C; Zhou, W; Mshale, B; Mwangi, E; Petrokofsky, G. (Springer, 2014)
Property rights to natural resources comprise a major policy instrument for those seeking to advance sustainable resource use and conservation. Despite decades of policy experimentation and empirical research, however, systematic understanding of the influence of different property rights regimes on resource and environmental outcomes remains elusive. A large, diverse, and rapidly growing body of literature investigates the links between property regimes and environmental outcomes, but has not synthesized theoretical and policy insights within specific resource systems and especially across resource systems. Here we provide a protocol for conducting a systematic review that will gather empirical evidence over the past two decades on this topic. We will ask the following questions: a) What are the environmental impacts of different property regimes in forests, fisheries, and rangelands? b) Which property regimes are associated with positive, negative or neutral environmental outcomes? c) How do those environmental outcomes compare within and across resource systems and regions?We will assess current knowledge of the environmental impacts of property rights regimes in three resource systems in developing countries: forests, fisheries and rangelands. These resource systems represent differing levels of resource mobility and variability and capture much of the range of ecosystem types found across the globe. The review will use a bundle of rights approach to assess the impacts of three main property regimes—state, private, and community—as well as mixed property regimes that involve some combination of these three. Assessment of the impacts of property rights regimes across a range of different resource systems and ecosystem types will enable exploration of commonalities and differences across these systems. Our analysis will emphasize major insights while highlighting important gaps in current research.